Information technology capability services that support organisational innovativeness in agriculture companies - Vosloo, Abraham (Department of Computer Science, 2026)
Organisations require the ability to continuously adapt to their changing operating environments to remain relevant. Specifically, agriculture companies operate in environments characterised by fast-changing markets and environmental conditions. Organisational innovation (OI) allows these agriculture organisations to evolve their way of work. Successful OI requires support from various internal and external stakeholders to a firm, and the IT capability has been recognised as a key enabler for organisational-wide innovation. With the fast-paced change across an organisation's digital and technology layers, the IT capability is expected to be more exposed to new technology advancements as a technology-supporting function compared to traditional non-technical capabilities. Thus, a deeper understanding of business practices that drive OI and the IT services that support OI-focused practices is needed. Multi-case studies were conducted across two agriculture organisations perceived to be successful in their innovation ambitions. The study comprised 12 face-to-face interviews across the case organisations and documented case organisation artefacts collected as part of the study. Only experienced personnel and senior leadership formed part of the study. Cross-case analysis was performed to compare the findings between the two case organisations. The findings of this study describe six OI-focused business practices that drive continual innovativeness in agriculture organisations. The study further describes five IT services utilised by agriculture organisations. Finally, the study describes the IT services that directly support the OI-focused business practices in agriculture organisations. The findings provide a deeper understanding of the interplay between the IT capability and OI. The findings also enable agriculture organisational leadership to prioritise and capacitate OI business practices to support innovation success. The study further supports IT leaders to focus on effectively executing the specified IT services that support OI-focused business practices.